1977
DOI: 10.1128/iai.17.2.290-295.1977
|View full text |Cite
|
Sign up to set email alerts
|

Infection of HeLa cells with Salmonella typhimurium 395 MS and MR10 bacteria

Abstract: After interaction with HeLa cells cultured in vitro, the fraction of adhering extracellular and that of internalized smooth Salmonella typhimurium 395 MS and rough 395 MR10 have been determined by two different techniques. (i) By using the indirect fluorescent-antibody technique on unfixed and acetone-fixed HeLa cell preparations, intracellular bacteria were considered to become stained only after acetone fixation. (ii) Based on the assumption that gentamicin affects only extracellular bacteria, disintegration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Attachment of bacteria to mucous membranes of alimentary (16), urinogenital (36), and respiratory tracts, is believed to be mediated by cell surface adhesins of the respective pathogens and receptors on the host cell-surface (4). Reports on in vitro attachment of S. typhimurium strains and LPS-deficient mutants, to macrophages (14), granulocytes (34) and HeLa cells (17,19,20) have shown that the LPSdeficient variants have higher affinity for the cells. Furthermore, expression of cell-surface hydrophobicity and negative charge seem to enhance the interaction of S. typhimurium with these cells.…”
mentioning
confidence: 99%
“…Attachment of bacteria to mucous membranes of alimentary (16), urinogenital (36), and respiratory tracts, is believed to be mediated by cell surface adhesins of the respective pathogens and receptors on the host cell-surface (4). Reports on in vitro attachment of S. typhimurium strains and LPS-deficient mutants, to macrophages (14), granulocytes (34) and HeLa cells (17,19,20) have shown that the LPSdeficient variants have higher affinity for the cells. Furthermore, expression of cell-surface hydrophobicity and negative charge seem to enhance the interaction of S. typhimurium with these cells.…”
mentioning
confidence: 99%
“…With conventional bright field light microscopy it is impossible to distinguish accurately intracellularly located from extracellularly attached bacteria. To overcome this obstacle, several indirect methods have been developed, e.g., antibiotic treatment to eliminate extracellular bacteria (13,17), optical sectioning through the cells by light microscopy (13), differential interference contrast microscopy (1, 2), identification of cell-adherent bacteria by immunofluorescence microscopy (4,11), and fluorescence quenching technique (9). However, these methods are not exact, and sometimes they lead to artifacts.…”
mentioning
confidence: 99%
“…Five years later, Giannella et al (5) noted the ability of S. typhimurium to invade HeLa cells. Since then, several investigators analyzed the invasive potential and morphology of the invasion of S. typhimurium in HeLa cell cultures (7)(8)(9)(10)(11)(12). As the first step in our attempt to clarify the invasive potential of S. typhi, HeLa cell monolayers were challenged with eleven S. typhi strains from different sources.…”
mentioning
confidence: 99%